2013
DOI: 10.1080/21501203.2013.877990
|View full text |Cite
|
Sign up to set email alerts
|

Muscodor kashayumsp. nov. – a new volatile anti-microbial producing endophytic fungus

Abstract: Muscodor kashayum (MycoBank no.: MB 803800; GenBank no.: KC481680) is a newly described endophytic fungus of a medicinal plant Aegle marmelos (Bael tree), growing in the tropical conserved rainforest in the Western Ghats of India. Muscodor kashayum possesses distinct morphological, molecular and physiological features from the earlier reported Muscodor species. The fungus forms characteristic rings of the ropy mycelium on potato dextrose agar medium. This sterile fungus is characterised by the presence of a pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 19 publications
1
32
0
1
Order By: Relevance
“…The tree showed a monophyletic group divided into two infrageneric clades (I and II), as previously observed (Zhang et al, 2010;Meshram et al, 2013;Saxena et al, 2014). Clade I harbors the vast majority of Muscodor species and is subdivided in three subclades (Fig.…”
Section: Isolation and Identification Of M Albus Aa3 From Wild Pineasupporting
confidence: 61%
See 2 more Smart Citations
“…The tree showed a monophyletic group divided into two infrageneric clades (I and II), as previously observed (Zhang et al, 2010;Meshram et al, 2013;Saxena et al, 2014). Clade I harbors the vast majority of Muscodor species and is subdivided in three subclades (Fig.…”
Section: Isolation and Identification Of M Albus Aa3 From Wild Pineasupporting
confidence: 61%
“…Analyses of VOCs composition demonstrated that the isolate aa3 produces naphthalene and azulene derivatives (e.g. aMuurolene and a-Guaiene), chemicals also detected among VOCs emitted by several isolates of M. albus (Atmosukarto et al, 2005;Ezra et al, 2004;Strobel et al, 2007Strobel et al, , 2001, but absent in the volatile mixtures produced by M. crispans (Mitchell et al, 2010), M. cinnamomi (Suwannarach et al, 2010), M. musae, M. oryzae (Suwannarach et al, 2013), M. kashayum (Meshram et al, 2013) and M. darjeelingensis .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Over the course of exploration of endophytic fungal resources, a total of 21 Muscodor species were recorded to date: M. albus (Worapong et al., ), M. roseus (Worapong, Strobel, Daisy, & Castillo, ), M. vitigenus (Daisy et al., ), M. crispans (Mitchel, Strobel, Hess, Vargas, & Ezra, ), M. yucatanensis (Gonzalez et al., ), M. fengyangensis (Zhang et al., ), M. cinnamomi (Suwannarach, Bussaban, Hyde, & Lumyong, ), M. sutura (Kudalkar, Strobel, Riyaz‐Ul‐Hassan, Geary, & Sears, ), M. equiseti , M. musae , M. oryzae , and M. suthepensis (Suwannaracha et al., ), M. kashayum (Meshram, Kapoor, & Saxena, ), M. darjeelingensis (Saxena, Meshram, & Kapoor, ), M. strobelii (Meshram, Saxena, & Kapoor, ), M. heveae (Siri‐udom, Suwannarach, & Lumyong, ), M. indicus and M. ghoomensis (Meshram, Gupta, & Saxena, ), M. tigerii (Meshram, Gupta, & Saxena, ), M. coffeanum (Hongsanan et al., ), and M. camphorae (Meshram, Kapoor, Chopra, & Saxena, ). In a previous study of endophytic fungi from Oryza granulata collected from Xishuangbanna, southwest China, which is an area known to contain rich fungal biodiversity, we isolated two Muscodor strains (Yuan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many novel species of the genus Muscodor (M. cinnamomi, M. equiseti, M. musae, M. oryzae, and M. suthepensis) were isolated from diverse plant hosts growing in northern Thailand (Suwannarach et al 2010;2013a). Other species of Muscodor have been isolated from tropical trees and vines in Australia, Central and South America, and Central, South and Southeast Asia (Meshram et al 2013;Suwannarach et al 2013a;Saxena et al 2015), while a previous report showed that Penicillium, Pestalotiopsis and Trichoderma were the most frequently isolated fungi from rubber trees (Gazis and Chaverri 2010). However, a diversity study of the genus Muscodor that lives in association with rubber trees has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%